Haar type bases in lorentz spaces via extrapolation - Nowak, Luis Maria Ricardo (2012)
In this note we consider Haar type systems as unconditional bases for Lorentz spaces defined on spaces of homogeneous type. We also give characterizations of these spaces in terms of the Haar coefficients. The basic tools are the Rubio de Francia extrapolation technique and the characterization of weighted Lebesgue spaces with Haar bases.